José Simeão Leal: escritos de uma trajetória - Oliveira, Bernardina Maria Juvenal Freire de (2009)
This research is related to temporality and singularity of the studied object which is based on historical data unveiled by means of remains and evidence, constituting the sources of a history from José Simeão Leal´s private personal archive considered in its whole dimension. Among the several primary sources which make up the archive, there are two thousand and seven letters exchanged between José Simeão Leal and his correspondents, especially the men of letters from his time (1929 to 1996); the handwritten dedication, contained in his office s books; the Cultural Notebooks, examples of his editorial production. The research emphasizes the editorial production, correspondence among men of letters, friends and members of the household as well as the plastic production, followed by criticism made in the journalistic press, and other documents which describe his production s art. Thus, José Simeão Leal´s route is built as well as his history and contribution to Brazilian culture having as theoretical-methodological framework the self-practices , legitimation, documentation, permanence, accessibility and immediate irruptions fundamentals crystallized in a reading and writing gesture. The self-writing is meant to be revealed, establishing a net of meanings, discoveries and construction of his autobiography based on his private personal archive. The examination of this whole archive enables to assure that José Simeão Leal developed a conclusive work for the Brazilian history and culture and for doing so, he molded his intellectual self-image, which is rewritten in this study as a biographic essay.